2019
DOI: 10.3389/fgene.2018.00732
|View full text |Cite
|
Sign up to set email alerts
|

FTO Knockout Causes Chromosome Instability and G2/M Arrest in Mouse GC-1 Cells

Abstract: N6-methyladenosine (m6A) is the most abundant modification on eukaryotic mRNA. m6A plays important roles in the regulation of post-transcriptional RNA splicing, translation, and degradation. Increasing studies have uncovered the significance of m6A in various biological processes such as stem cell fate determination, carcinogenesis, adipogenesis, stress response, etc, which put forwards a novel conception called epitranscriptome. However, functions of the fat mass and obesity-associated protein (FTO), the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Mechanistically, FTO has been demonstrated to suppress the m6A methylation of ubiquitin specific peptidase 7 while increasing mRNA stability via mRNA demethylation (33). These results indicate that FTO may promote oncogenesis and that suppressing its expression may offer a beneficial therapeutic strategy for various types of cancer.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mechanistically, FTO has been demonstrated to suppress the m6A methylation of ubiquitin specific peptidase 7 while increasing mRNA stability via mRNA demethylation (33). These results indicate that FTO may promote oncogenesis and that suppressing its expression may offer a beneficial therapeutic strategy for various types of cancer.…”
Section: Discussionmentioning
confidence: 92%
“…Although FTO seemed to promote proliferation of HepG2 cells, it was also observed that this does not significantly affect apoptosis. Huang et al (33) demonstrated that FTO depletion decreases the expression levels of the mitotic checkpoint complex and G2/M regulators in mouse GC-1 cells. Wu et al (34) observed that FTO knockdown markedly decreases the expression levels of cyclin A2 and CDK2, both crucial cell cycle regulators, leading to delayed entry of methylene diphenyl diisocyanate-induced cells into G2 phase.…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…This relationship needs to be experimentally verified in future studies. However, knockdown of FTO, an m6A regulatory gene, inhibits cell cycle progression by increasing m6A levels of BUB1B and CCNA2 genes, thereby inhibiting their expression [ 76 , 77 ]. Interaction between IGF2BP1 and KIF11 alters localization of β-actin mRNA, thereby inhibiting cell migration [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of FTO in GC‐1 cells shows that the cell cycle is retained at the G2/M phase. In addition, the expression of the MCC complex which has the function of maintaining chromosome stabilization is decreased (Huang et al., 2019). This finding reveals that FTO regulates chromosome segregation and cell cycle progression via m 6 A demethylase activity (Huang et al., 2019).…”
Section: Aberrant Rna Methylation During Spermatogenesismentioning
confidence: 99%
“…In addition, the expression of the MCC complex which has the function of maintaining chromosome stabilization is decreased (Huang et al., 2019). This finding reveals that FTO regulates chromosome segregation and cell cycle progression via m 6 A demethylase activity (Huang et al., 2019). Further m 6 A‐IP‐qPCR and RNA degradation experiments proved that deletion of the FTO will affect the regulation of m 6 A‐modified target genes, thereby affecting mRNA stability (Huang et al., 2019).…”
Section: Aberrant Rna Methylation During Spermatogenesismentioning
confidence: 99%